The Effect of Quality Service and Price Perceptions on Customer Satisfaction and its Implications For Repurchase Intentions of PT Pos Indonesia (Persero) Courier Service Customers - Agus Fatkhurohman Handoyo; Vanessa Gaffar; Adhistian, Patria; Priyo Wibowo (CV. Ulil Albab Corp, 2025)
Quality Service and perceived service price determine customer satisfaction. Quality Service and perceived service price also have an impact on customer repurchase intentions. Satisfied customers tend to repurchase goods and services. This research aims to analyse the influence of Quality Service and price perception on customer satisfaction and the implications for customer repurchase intentions. The population in this study were users of PT Pos Indonesia Persero services in the Regional 2 Jakarta work area. The sampling technique is to use a simple random sampling method. The type of data used is primary data with questionnaires and secondary data with literature. The analysis tool used is Path Analysis, with Lisrel. The results of the research found that there is a direct influence between the Quality Service variable and the price perception variable on the customer satisfaction variable, there is a direct influence between the Quality Service variable, the price perception variable and the customer satisfaction variable on the intention to repurchase, and there is an indirect influence between the Quality Service variable and price perception variable on repurchase interest variable through the intervening variable customer satisfaction